The Effect of Moringa Leaf Extract on Creatinine and Uric Acid Levels in Hyperlipidemia Conditions: Pengaruh Ekstrak Daun Kelor Terhadap Kadar Kreatinin dan Asam Urat Pada Kondisi Hiperlipidemia - Rahmatika Fitria Ayu Prayekti; Puspitasari Puspitasari (Universitas Muhammadiyah Sidoarjo, 2026)
Hyperlipidemia is a lipid metabolism disorder characterized by elevated levels of cholesterol, triglycerides, and low-density lipoprotein (LDL), which can lead to increased creatinine and uric acid levels due to impaired kidney function and oxidative stress. Moringa leaves (Moringa oleifera) are known to contain flavonoids, phenolics, and antioxidants that have the potential to improve these conditions. This study aims to determine the effect of moringa leaf extract on creatinine and uric acid levels in male Wistar strain white rats with hyperlipidemia. The study was conducted from May to June 2026, using a pretest-posttest control group design with five treatment groups of hyperlipidemic rats: a negative control, a positive control (simvastatin at a dose of 0.18 mg/200 g body weight), and moringa leaf extract administered at doses of 100 mg/200 g body weight, 150 mg/200 g body weight, and 200 mg/200 g body weight. The results of the Two-Way ANOVA test showed that creatinine and uric acid levels decreased in all groups after treatment. The time factor (before and after treatment) showed a significant difference (p<0.001), but between treatment groups did not show a significant difference in creatinine levels p=0.113 or uric acid levels p=0.096 (p>0.05). In conclusion, the administration of Moringa oleifera leaf extract has an effect on reducing creatinine and uric acid levels in male white rats of the Wistar strain with hyperlipidemia, but there was no significant difference in effectiveness between treatment groups.